The environmental, economic, and social development impact of desertification in Iraq: a review on desertification control measures and mitigation strategies - Al-Obaidi, Jameel R.; Allawi, Mohammed Yahya; Al-Taie, Bilal Salim; Alobaidi, Khalid H.; Al-Khayri, Jameel M.; Abdullah, Sumaiyah; Ahmad-Kamil, E. I. (Springer, 2022)
The threat of desertification is considered a global concern that occurs in many environments in different parts of the world, where extensive lands are transformed gradually into desert or semi-desert areas, and this causes economic and health issues. Iraq and many other parts of the Middle East are facing desertification threats in the last twenty years. Despite the significance of this issue, relevant reviews are scarce. The removal of vegetation cover, overgrazing, deforestation in times of war, poor irrigation practices and water scarcity are some of the main causes of desertification in Iraq. Fighting desertification requires cooperative efforts including the utilization of innovative practices, biotechnological approaches, restoration of oases, continuous reforestation, and rehabilitation of agricultural lands. The objective of this review article is to discuss the causes of desertification and land degradation in Iraq, highlighting the main natural and human factors involved, and the consequent impact on the national security, economy, society, and health. In addition, it suggests recommendations for policies and actions that can be integrated to mitigate this problem.